Shifting the Centre: The Transformation of Greenlandic Society from Subsistence to Market Economy in the Nineteenth Century - Robakiewicz, Zoe (Culture and History: Student Research Papers, 2024)
In this article, I aim to illustrate the process of transforming Greenlandic society from one centered around a subsistence economy to one integrated into the external Danish market, drawing particularly on Karl Polanyi’s characterization of market patterns. My focus will be on the means by which the colonial administration acquired a socio-economic dominant position in Greenland, the colonial reforms implemented during the nineteenth century, and the establishment of forstanderskaberne, local councils of representatives, as a pivotal milestone in the transformation of the Indigenous society.